Prince's reunion in paradise - Acheampong, Faye (Harlequin romance, 2024)
"Pop princess to future queen? Crown Prince Dorian's Maldives holiday was supposed to be an escape. But he soon discovers that even paradise isn't problem-free when he's unexpectedly reunited with Damica Foye--retired pop star and his childhood pen pal. AS a teenager, Dorian found solace in Damica's understanding of the pressure that being in the limelight creates. Then duty called for Dorian, fame became too much for Damica to bear and their bond began to break... Now, stuck on an island, will they claim their second chance and, this time, build more than just a friendship?" -page [4] of cover